Strategies For Implementing Activity Priority Analysis (APK) To Achieve Good Governance In Indonesia - Ihwan Arifuddin; Jumadi; Muhammad Yamin; Wahira; Andi Kasmawati (International Journal of Economics Accounting and Management, 2025)
Local government budgets in Indonesia often fail to translate planned development objectives into actual outcomes. This study investigates how entrenched budget politics – the interplay of political interests, corrupt networks, and weak fiscal rules – creates a persistent gap between planned and actual budgets. A review of recent studies shows that pervasive “budget leakage” and interest-group capture divert public funds away from priority services and misallocate scarce resources. We articulate the research gap: while public financial management is well studied, few analyses focus on the political dynamics of local budgeting or why reforms fail to curb corruption. Using Dunn’s policy evaluation framework (with criteria such as effectiveness, efficiency, adequacy, responsiveness, and appropriateness), we propose a systematic evaluation of local budgets. We empirically analyze Indonesian subnational deficits (exceeding statutory caps) to illustrate flawed fiscal policies. We then explore the causes of misaligned programs: incumbent leaders exploit loopholes (e.g., padded grants in election years) and finance deficits for votes. We demonstrate how the current planning system allows for political capture by citing examples of inflated project lists and unimplemented “ghost” programs. As a solution, we describe an Activity Priority Analysis (APK) – a multi-stakeholder, evidence-based budgeting process where government, academia, and civil society collaboratively vet and rank programs. We outline the evaluation steps using Dunn’s criteria to judge budget outcomes. The diagrams illustrate the proposed APK workflow.